Developing English Writing Materials Based on Scientific Approach in Descriptive Text For Grade Students X of SMAN 1 Kolang (The Explora, 2022)
This research aims to develop writing material for students of SMAN I Kolang class ten. The research problem is Which writing materials are suitable to be developed for SMAN I Grade Students X Kolang students based on a scientific approach in a text descriptive. The goal of this study is to know the appropriate writing materials that need to be developed by SMAN 1 Grade X Kolang students based on a scientific approach in a descriptive text. The data collected is by giving an interview to the English teacher and spreading the questionnaire to 36 students, where the results of interviews and questionnaires show that students. need to write English that contains the knowledge and the topics appropriate to the curriculum and the student's level, material of writing developed, namely descriptive text. Research design Sugiyono (2008). The uses of Research and Development (R&D) have gone through the 3 theoretical phases: Preliminary study, design, and the development of a model of writing material. The material of new writing was passed by the two experts. Based on the expert judgment results, the score was 87 06, which belonged to a good category in Dirgeyasa (2011), as the range is 670-89). The result of the investigation of this find is that the materials to be developed are the tourist attractions and history, boldness of Unit Lin terms of content, presentation, language, and graphics.